KURIKULUM PENDIDIKAN ISLAM MENURUT SYED MUHAMMAD NAQUIB AL-ATTAS DAN RELEVANSINYA TERHADAP KURIKULUM SISTEM PENDIDIKAN NASIONAL - Adam Azizi; Arizqi Ihsan Pratama; M. Yogi Saputra (JIP: Jurnal Ilmu Pendidikan, 2025)
Syed Muhammad Naquib al-Attas is one of the leading Muslim intellectuals who introduced significant reforms in the field of Islamic education. The primary objective of this research is to examine al-Attas’s concept of curriculum and its relevance to the curricula implemented in Islamic educational institutions in Indonesia. The purpose of the study is to gain an in-depth understanding and analysis of Islamic education from the perspective of Syed Muhammad Naquib al-Attas.This research employs a qualitative descriptive method with a library research approach, focusing on the collection of data from various relevant sources. These sources include books and previous studies related to the topic of this academic work. The findings of the study reveal that, according to al-Attas, the concept of an Islamic education curriculum, encompassing components such as objectives, content, teaching methods, and evaluation, aligns with the educational curriculum used in Indonesia. Al-Attas asserts that the ultimate goal of Islamic education is to cultivate a virtuous human being. This educational objective resonates with the goals of Islamic education in Indonesia, which aim to nurture individuals who possess faith in God Almighty and exhibit exemplary moral character.